HOW TO USE NEW METHODS OF TEACHING - Ergasheva Shakhnoza Tashkent district Tashkent region , vocational school teacher (SCIENCE AND INNOVATION IDEAS IN MODERN EDUCATION, 2024)
Before considering how to teach English to beginners, we need to understand who beginners are in language learning contexts. A true beginner has zero knowledge of a language, which is rare with a language as prevalent as English. You’re more likely to encounter false beginners on your teaching journey. These learners have some knowledge of the language that they may have acquired at school, through media, or with self-study. However, their knowledge is so limited that they need to start from square one. The Ministry of Preschool Education has been instructed to develop, jointly with UNICEF, and implement guidelines for teaching foreign languages ​​to children under the age of 7. The main attention at the meeting was paid to training specialists for the higher education system.[1] Key words. Methods, interactive